Diskursus Edukasi Literasi Digital Di Youtube: (Analisis Wacana Kritis Norman Fairclough Terhadap Kanal Youtube @pertajampolapikir) - Rifqi Syahlendra; Masriah; Rafli Akram Kurniansyah; Devi Novianti; Riskya Khairunisa Novitasari (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2026)
This study aims to analyze how the construction of digital literacy education discourse is formed in the YouTube content of @PertajamPolapikir, identify the ideologies and representations that emerge within it, and understand the educational communication strategies used in building digital literacy awareness among internet users. The method used is a qualitative approach with Norman Fairclough's Critical Discourse Analysis (CDA), which covers three dimensions: text, discourse practice, and social practice. Data were collected through video observation, documentation, and literature review. The results show that in the text dimension, the use of metaphors demonstrates dramatization that frames digital addiction and mental health. In discourse practice, content is produced systematically combining popular language and semi-scientific legitimacy to strengthen persuasive power. And in socio-cultural practice, discourse reflects the power relations between platforms and users in the context of digital culture.